Application of supercritical fluid extraction coupled with counter–current chromatography for extraction and online isolation of unstable chemical components from Rosa damascena. Issue 13 (1st July 2013) - Li, Sainan; Guo, Liping; Liu, Chunming; Zhang, Yuchi
<x xml:space="preserve">Abstract</x> Supercritical fluid extraction (SFE) coupled with high‐speed counter‐current chromatography (HSCCC) was successfully used for the extraction and online isolation of the unstable compounds from Rosa damascene in a single extraction and separation operation in two stages. The solvent systems of SFE/HSCCC were optimized with the help of multiexponential function model. At the first stage, the upper phase of the solvent system of n‐butanol–tert‐butyl methyl ether–acetonitrile–0.1% aqueous TFA (1.7:1.0:0.8:4.0, v/v/v/v) was used as both the SFE entrainer and the HSCCC stationary phase, and the target compounds were eluted with the corresponding lower phase to separate the hydrophobic compounds. At the second stage, the upper phase of the solvent system of n‐hexane–ethyl acetate–methanol–water (3.2:1.0:2.8:2.6, v/v/v/v) was used as both the SFE entrainer and the HSCCC stationary phase, followed by elution with the corresponding lower phase to separate the moderate hydrophobic compounds. Six compounds including formononetin, delphinidin, cyaniding, 5, 6, 4′‐trihydroxy‐7, 8‐dimethoxy flavone, 5, 3′‐dihydroxy‐7, 8‐dimethoxy flavone, and 5‐hydroxy‐6, 7, 8, 3′, 4′‐pentamethoxy flavone were successfully separated in one extraction–separation operation within 300 min. The targeted compounds were identified by MS and NMR spectroscopy. This research has opened up great prospects for industrial application of SFE/HSCCC to the extraction and separation of unstable compounds.